THE EFFICIENCY OF SUPPLIES CHARGING TIME GILL NET AT FISHING PORT DUMAI CITY RIAU PROVINCE - Rendra Triardi; Jonny Zain; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTRendra_triardi@yahoo.comThis study was conducted in July 2014 at fishing port Dumai city. Thepurpose of this study was to determine the extent of charging time efficiencyfishing supplies fishing boat gill nets by using the survey method.The results showed that the level of efficiency of the supplies chargingtime at fishing port Dumai City ranged from 53.45% to 87.37% with an averageof 67.96% and a relatively less efficient. The factors that affect the level ofefficiency of the supplies charging time is the amount of fuel (X1), water (X2), ice(X3), ABK (X4), time wasted (X5), and the size of the fishing vessel (X6). Byusing multiple regression analysis of the obtained value Y = 88,487 + 0,011 X1 +0,081 X2 - 1,164 X3 - 4,339 X4 – 0,631 X5 + 3,346 X6. Relationship is positivefor efficiency is the amount of fuel, water, and the size of the vessel, while therelationship is negative is the amount of ice, crew, and time wasted. Theserelationships have a strong correlation (R = 0.911) and an impact on the efficiencyof the supplies charging time.Keywords : Efficiency, Gill Net, Supplies Charging Time1)